2001
DOI: 10.1046/j.1439-0329.2001.00231.x
|View full text |Cite
|
Sign up to set email alerts
|

Formation and growth of stem cankers caused by Gremmeniella abietina on young Pinus contorta

Abstract: From 1990 to 1995, the formation and growth of stem cankers caused by Gremmeniella abietina on Pinus contorta var. latifolia was studied in three stands in northern Sweden. The stands were planted in 1976±80. The total number of cankers on 756 trees that were individually followed increased from 233 to 477 during the 5-year period. With 42.0% of the cankers, the pathogen entered through or from the base of diseased branches, and 33.6% through visually undamaged bark. Most of the cankers were within 100 cm of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…Witzell, A. Bernhold and P. Hansson The results of this study show that the vitality of G. abietina conidia in P. sylvestris slash on ground in northern boreal areas remain high the entire period from felling of infected trees until conidia dispersal. This saprotrophic ability agrees with earlier findings from Fennoscandia, concluding that G. abietina can survive and reproduce for at least 2 years in dead shoots of living trees (Hellgren and Barklund 1992;Kaitera et al 1997), and even longer in cankers (Kurkela 1981;Witzell 2001). Our results are also similar to those of Dorworth (1972) who showed that apothecia of the North American race of G. abietina are able to survive for at least 10 months on Pinus resinosa slash.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…Witzell, A. Bernhold and P. Hansson The results of this study show that the vitality of G. abietina conidia in P. sylvestris slash on ground in northern boreal areas remain high the entire period from felling of infected trees until conidia dispersal. This saprotrophic ability agrees with earlier findings from Fennoscandia, concluding that G. abietina can survive and reproduce for at least 2 years in dead shoots of living trees (Hellgren and Barklund 1992;Kaitera et al 1997), and even longer in cankers (Kurkela 1981;Witzell 2001). Our results are also similar to those of Dorworth (1972) who showed that apothecia of the North American race of G. abietina are able to survive for at least 10 months on Pinus resinosa slash.…”
supporting
confidence: 92%
“…latifolia Engelm. by killing young shoots and buds and by causing necroses on the stem resulting in cankers (Roll-Hansen 1964;Kurkela and Norokorpi 1979;Hellgren and Barklund 1992;Karlman et al 1994;Witzell 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Apothecia can also be found concentrated to stem cankers (e.g. on Pinus contorta ; Witzell, ). Apothecia are brown cuplike, 1 mm with short stalks and ascospores are colourless, ellipsoid, four‐celled, often slightly curved with rounded ends and 15–22 × 3–5 μm (Sinclair and Lyon, ).…”
Section: Pest Categorisationmentioning
confidence: 99%
“…Stem cankers on pole-sized trees (LTT G. abietina) are rare in Sweden but common in North America on the highly susceptible P. resinosa (Skilling et al 1986;Laflamme 1991). However, stem cankers on smaller trees are more common and have caused severe damage to P. contorta plantations in northern Sweden (Karlman et al 1994;Witzell 2001).…”
Section: Introductionmentioning
confidence: 99%